Use of moringa, Moringa oleifera leaf meal as partial replacement of soybean meal in common carp feed - Al-Dubakel, Adel Y.; Taher, Majid M. (Iraqi Journal of Aquaculture, 2021)
A laboratory experiment was conducted to investigate the replacement of soybean meal with moringa, Moringa oleifera (Author's name and year) leaf meal (MLM) in the formulated diet of common carp, Cyprinus carpio. Eight aquaria, two for each treatment, were used for the current experiment conducted at the Laboratory of Live Food- Aquaculture Unit- Agriculture College. Four treatments which were control (C) (0% MLM), T1 (5% MLM), T2 (10% MLM) and T3 (15% MLM) were used in feeding common carp. This experiment lasted 56 days and fishes were fed six days a week using 5% of fish weights as feeding ratio. Statistical analysis of weight increments and daily growth rate proved that there were significant differences (P≤0.05) between T3 and other treatments, while there were no significant differences (P>0.05) between C and both T1 & T2. Best feed conversion rate (3.13) achieved by fishes fed on feed with 5% moringa leaf meal (T1), while the worst feed conversion rate (7.50) was achieved by fishes fed on feed with 15% moringa leaf meal (T3). In conclusion that better growth and feed conversion rate achieved by fishes fed on feed with 5% moringa leaf meal and increasing the ratio in the feed will affect adversely the results.